The Role of The Camara Nusantara Livestock Ship in Volatility and Disparity of Beef and Cattle Prices in Indonesia - Tri Melasari; Budi Guntoro; Mujtahidah Anggriani Ummul Muzayyanah (Journal of Global Innovations in Agricultural Sciences)
This study examines how livestock ships affect price volatility and disparity at the producer and consumer levels. East Nusa Tenggara (ENT) is one of the provinces in Indonesia that experiences a beef surplus. Nationally, Jakarta and East Kalimantan are the provinces that experience the 2nd and 4th beef deficits. Livestock distribution is an expected method to reduce the volatility and disparity of live cattle and beef prices. The ARCH/GARCH model is used in analyzing volatility and forecasting food and agricultural commodity prices. Based on the results of the ARCH/GARCH analysis, livestock ships have not been effective in reducing producer price volatility in East Nusa Tenggara and consumer prices in Jakarta and East Kalimantan before the presence of livestock ships (January 2010-December 2015) and after the presence of livestock ships (January 2016-December 2023). The results show that CN Livestock Ships have not been effective in reducing consumer price volatility in both Jakarta and East Kalimantan and also producer prices in ENT and East Kalimantan. Based on the results of the variation coefficient analysis, livestock ships are effective in reducing price disparities between producers (in ENT) and consumers (in East Kalimantan) centers. The smaller the coefficient of variance of a data group, the more homogeneous the data is and this means that the price is more stable or does not fluctuate This ineffectiveness is influenced by the conditions of the COVID-19 pandemic and ship docking. The price disparity decreased due to lower transportation costs using livestock ships. Referring to this, efforts to increase the effectiveness of the Camara Nusantara livestock ship must be viewed comprehensively. In addition to increasing the operational capacity of livestock ships by increasing the number of fleets and improving ports and other supporting infrastructure, the government also needs to look at the role of inter-island livestock traders, slaughterhouse facilities and wholesalers (distributors, importers) to jointly utilize the Camara Nusantara livestock ship in order to stabilize beef prices both at the producer and consumer levels. Keywords: Camara Nusantara livestock ship, beef price, volatility, disparity, ARCH, GARCH.